Chinese process safety management core elements and control measures. Issue 4 (22nd January 2017) - Zhou, Aitao; Fan, Lingpeng; Ma, Mingfei; Tao, Bo
Abstract : With the popularization and application of chemical process safety management (PSM) systems in the chemical industry, the use of such systems in China has become the focus of a large volume of research. In this article, 12 elements included in the current Chinese PSM system are divided into four stages from a structural point of view. This division will be helpful in the follow‐up analysis. After a careful analysis of the evaluation results for one PSM pilot study in Nanjing, some correlations have been found between the results of the elemental evaluation. Small‐ and medium‐sized chemical plants make up a large proportion of Chinese chemical plants and many chemical accidents take place in these plants, so a simplified PSM system in practical operation need to be found. Based on a previous PSM structural analysis, the secondary elements of the PSM system can be removed. This allows researchers to avoid the traditional method of analyzing PSM elements individually. In the concrete analysis process, a theoretical analysis of the correlation degree between elements can be combined with the results of accident investigations. The simplified Chinese PSM system consists of four core elements: Process safety information, process hazard analysis, training, and emergency management. Based on the current applications of these four core elements in China, a consideration of correlations between these elements is used to make several suggestions for improving China's PSM systems. © 2017 American Institute of Chemical Engineers Process Saf Prog 36: 378–381, 2017